2022
DOI: 10.1186/s12888-022-04365-5
|View full text |Cite
|
Sign up to set email alerts
|

A Czech version of the Overall Anxiety Severity and Impairment Scale (OASIS): standardization and psychometric properties

Abstract: Background The Overall Anxiety Severity and Impairment Scale (OASIS) is a transdiagnostic measure that assesses severity and impairment associated with anxiety disorders. However, its psychometric properties were primarily examined in English-speaking or western countries. Therefore, this study aims to examine its psychometric parameters in the Czech Republic. Methods A large representative sample (n = 1738), a clinical sample (n = 57) and a retest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It has been argued that covariance between items 1 and 2 is theoretically plausible because the responses are partly contingent on each other (i.e., if frequency of anxiety is rated zero, severity should also be rated zero) 25 , 28 , 34 . Following this explanation, a method effect induces a so-called response dependency between these two items 74 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been argued that covariance between items 1 and 2 is theoretically plausible because the responses are partly contingent on each other (i.e., if frequency of anxiety is rated zero, severity should also be rated zero) 25 , 28 , 34 . Following this explanation, a method effect induces a so-called response dependency between these two items 74 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors have interpreted their findings as initial support for measurement invariance with respect to gender but recommended similar analyses in broader samples (e.g., primary care patients) since they have found a potential (nonsignificant) instance of DIF. Two other studies have investigated the Czech version of the OASIS for measurement invariance by means of multi-group CFAs 34 , 35 . In both studies, evidence was found that men and women responded similarly to the OASIS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations